Penetrating injury to the head: case reviews - Awang, Mohamed Saufi; Regunath , Kandasamy; SB, Siti; Premananda , M R; Tan, W M; Haron, R H (Malaysian Medical Associations, 2012)
Penetrating injury to the head is considered a form of severe traumatic brain injury. Although uncommon, most neurosurgical centres would have experienced treating patients with such an injury. Despite the presence of well written guidelines for managing these cases, surgical treatment requires an individualized approach tailored to the situation at hand. We describe a collection of three cases of non-missile penetrating head injury which were managed in two main Neurosurgical centres within Malaysia and the unique management approaches for each of these cases.